A silver functionalized ZIF-8 derived heterostructure with excellent visible-light-driven photocatalytic removal of antibiotics - Bhattacharyya, Puja; Pudake, Ramesh Namdeo; Chakrabarti, Sandip (Frontiers in Nanotechnology, 2025)
An effective silver (Ag) -modified zeolitic imidazolate frameworks- ZIF-8 derived heterostructure (Ag/ZnO/C) was prepared using the facile room temperature wet chemical method for the reduction of Ciprofloxacin under visible light irradiation. The synthesized Ag/ZnO/C microstructure was characterized by field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) analysis. X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and TEM morphological analysis confirmed the existence of metallic Ag in the resultant photocatalyst. The synergistic effect of the Metal–organic frameworks (MOF) - derived structure and metallic Ag nanoparticles depicts excellent degradation of Ciprofloxacin with high efficiency. Under optimum condition the efficiency was reached to 98% in 60 min under visible light irradiation. The apparent rate constant k is estimated as 58.04 × 10−3 min−1 depicting high photocatalytic performance. The scavenger experiment revealed the dominance of generated h+ and ⋅O2− in the photocatalysis mechanism. The large surface area and successful silver nanoparticle encapsulation on the material surface facilitates to the excellent efficiency of the material. Our findings open new robust possibilities to design a ZIF-8 based efficient photocatalyst for effective application in the field of photo-degradation.